Personalized medicine in interstitial lung diseases. Issue 3 (May 2017) - Spagnolo, Paolo; Oldham, Justin M.; Jones, Mark G.; Lee, Joyce S.
Abstract : Purpose of review: A number of recent studies have explored the possibility to apply personalized medicine to interstitial lung diseases (ILDs), particularly idiopathic pulmonary fibrosis (IPF), the most common and deadly of the idiopathic interstitial pneumonias. In our review, we summarize and discuss the most recent literature on personalized medicine in IPF as well as hypersensitivity pneumonitis and sarcoidosis, with emphasis on patient subgroups for which a personalized approach to disease prognostication and management may become a reality in the near future. Recent findings: Most of the studies that have explored the applicability of personalized medicine to ILDs have been conducted in patients with IPF. Such studies have suggested the existence of several distinct disease subgroups defined by similar genetic profiles, molecular pathways, exposures and individual lifestyles. Personalized medicine in hypersensitivity pneumonitis is in its infancy. The development and applicability of personalized medicine to sarcoidosis, on the other hand, remains problematic for several reasons, including the lack of a diagnostic gold standard, the highly variable and unpredictable disease course, particularly across patients of different ethnicities, the poor correlation between disease activity and disease severity and the lack of a validated management algorithm. Summary: A number of distinct patient subgroups have been identified in ILDs. Although available data need to be validated longitudinally, the possibility to study homogeneous groups of patients may allow prediction of disease behavior and response to treatment with dramatic clinical implications.